A investigação criminal, a polícia judiciária e o Ministério Público - Silva, Marcio Cesar Fontes (2006)
This Project deals with criminal investigation by both judicial police and Public Office in Brazil, with respect to their constitutional attribution to it. There is no doubt that the Constitution of the Republic attributed this function to the organs of Judicial Police, namely Federal and Civil (State) Police, in 1988. Nevertheless, the Public Office has ventured in this field, stating that they also have attributions, using various arguments, among them the theory of implicit powers, subconstitutional empowering, that is, the organic laws of the institution, since criminal investigation is not a exclusive attribution of Judicial Police, the Constitution does not forbid its carrying out by the Public Office. The whole project was done in the light of the Brazilian Constitution and subconstitutional current legislation, with reference to philosophy, history and jurisprudence. Initially, we tackle with a philosophical foundation of legal ordering the common good, society, justice and law, as they are basic for a correct understanding of the issue at stake. Next we establish the relevant constitutional premisses. Then we examine the founding of existence of penal process from the point of view of the instruments of right ensuring. After that we study the principles and penal procedural systems, within our philosophical and constitutional design. The research then moves to the functioning of criminal investigation in Brazil. Finally, we deal with the impossibility of Public Office to assume directing or directly performing criminal investigation, through the reasons that lead us to that conclusion, and considering that, in spite of not being an exclusive function of Judicial Police, the Constitution expressly foresees exceptions. The project also presents a critical view of the Public Office initiative in elaborating administrative acts, which represents an attempt to take over a function that the Constitution of Brazil attributes to Judicial Police, and a breaking of the current system in use